2005
DOI: 10.1158/1535-7163.mct-05-0262
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and TRAIL-mediated colon cancer cell death: the roles of p53, TRAIL receptors, and c-FLIP

Abstract: Tumor necrosis factor -related apoptosis-inducing ligand (TRAIL) has recently attracted attention as a potential therapeutic agent in the treatment of cancer. We assessed the roles of p53, TRAIL receptors, and cellular Fas-associated death domain -like interleukin-1B-converting enzyme inhibitory protein (c-FLIP) in regulating the cytotoxic effects of recombinant TRAIL (rTRAIL) alone and in combination with chemotherapy [5-fluorouracil (5-FU), oxaliplatin, and irinotecan] in a panel of colon cancer cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
116
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 37 publications
11
116
2
1
Order By: Relevance
“…One study reported TRAIL-enhanced apoptosis in response to chemotherapy in a large panel of colon cancer cell lines, including in the p53 Ăž / Ăž or p53 À/À HCT116 cells (Galligan et al, 2005). In contrast, our results are in favour of an antagonism between the two molecules in p53 wild-type cells such as HCT116, LS513 and LS174T.…”
Section: Discussioncontrasting
confidence: 79%
“…One study reported TRAIL-enhanced apoptosis in response to chemotherapy in a large panel of colon cancer cell lines, including in the p53 Ăž / Ăž or p53 À/À HCT116 cells (Galligan et al, 2005). In contrast, our results are in favour of an antagonism between the two molecules in p53 wild-type cells such as HCT116, LS513 and LS174T.…”
Section: Discussioncontrasting
confidence: 79%
“…In fact, this is in agreement with recent reports showing that chemotherapy-induced downregulation of cFLIP splice forms occurs in cell lines irrespectively of their p53 status and, more specifically, that ATM kinase activity is required to trigger 5-FU-and neocarzinostatin-induced and p53-independent cFLIP downregulation, which in turn sensitized hepatocellular carcinoma cell lines to TRAIL. 41,42 Identification of the factor regulated by the Ca 2 Ăž -CaM-p53 axis described in this report conducting DR5-DISC activity thereby remains.…”
Section: Discussionmentioning
confidence: 80%
“…The mRNA sequences targeted by c-FLIP L siRNA was 5 0 -AAGGAA CAGCTTGGCGCTCAA-3 0 , which was used in a previous study [33]. An unrelated siRNA with a sequence of 5 0 -AATTCTCCGAACGTGTCACGT-3 0 was also employed as a control [33].…”
Section: Rna Interferencementioning
confidence: 99%
“…The mRNA sequences targeted by c-FLIP L siRNA was 5 0 -AAGGAA CAGCTTGGCGCTCAA-3 0 , which was used in a previous study [33]. An unrelated siRNA with a sequence of 5 0 -AATTCTCCGAACGTGTCACGT-3 0 was also employed as a control [33]. CCRF-CEM cells were transfected with 2 lM of siRNA by electroporation using MicroPorator MP-100 according to manufacturer's instruction (NanoEn Tek Inc., Korea) [31], and downregulation of c-FLIP L expression was examined by Western blotting after incubation for 48 h. After 24 h of siRNA transfection, the cells (2 9 10 4 cells/well in 96-well plate) were treated with AY4 (10 lg/ml) or TRAIL (0.5 lg/ml) alone or in combination with SAHA (1 lM) or VPA (1 mM) for 24 h prior to MTT assay.…”
Section: Rna Interferencementioning
confidence: 99%